Amyopathic anti‐TIF1‐γ antibody‐positive dermatomyositis in a young man - Nicolas Kluger (JEADV Clinical Practice, 2024)
Abstract Dermatomyositis (DM) is a rare idiopathic inflammatory disorder characterized by the association of typical skin and myositis. It may be associated with interstitial lung disease and/or malignancy. Diagnosis is usually easy in patients with fair skin due to very peculiar clinical features, but, among persons of colour (PoC), diagnosis can become challenging for an unexperienced eye, especially in case of lack of clinical myositis. We present the case of a young man with amyopathic DM that has evolved for 4 years before the proper diagnosis has been made. Our case highlights the pitfalls related to the clinical presentation of DM in PoC.